Exploring the Dynamics of Venture Capital Funding in India's Fintech Sector: A Theoretical Assessment of Challenges and Opportunities in Banking, Financial Services, and Insurance Fintech Enterprises - Jisha M R, Dr.Rekha (South Eastern European Journal of Public Health, 2025)
This study delves into the intricate dynamics of venture capital (VC) funding for fintech companies in India, with a special focus on the Banking, Financial Services, and Insurance (BFSI) sectors. Utilizing secondary data and a theoretical framework, the paper explores the evolving trends in fintech investment, identifying key challenges fintech companies face in securing venture capital. These challenges span regulatory, market, and operational domains, underscoring the complexity of the fintech ecosystem. Concurrently, the paper examines the opportunities that innovation within the BFSI fintech landscape presents for venture capitalists. By providing a nuanced assessment of these opportunities and challenges, this research offers valuable insights into the strategic positioning of fintech companies and the factors that influence VC investment decisions in India's burgeoning fintech space.